2009
DOI: 10.1002/bjs.6615
|View full text |Cite
|
Sign up to set email alerts
|

Colonic lymphoid follicles and NOD2/CARD15 mutational status in Crohn's disease

Abstract: Patients with Crohn's disease and the NOD2/CARD15 mutation show a remodelling of CLFs in both uninvolved and actively inflamed intestines. These subjects may have a defective immune response by organized lymphoid structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…[16][17][18][19]. Prior studies observed that the number of lymphoid follicles are decreased in disease unaffected colon in CD patients [20,21]. The decreased expression of gene-probes in Cluster 1 is consistent with this observation and suggests that impaired development of lymphoid follicles represents an early pathogenic change in CD.…”
Section: Patient Characteristicssupporting
confidence: 78%
See 1 more Smart Citation
“…[16][17][18][19]. Prior studies observed that the number of lymphoid follicles are decreased in disease unaffected colon in CD patients [20,21]. The decreased expression of gene-probes in Cluster 1 is consistent with this observation and suggests that impaired development of lymphoid follicles represents an early pathogenic change in CD.…”
Section: Patient Characteristicssupporting
confidence: 78%
“…Five clusters (#5, 9,13,21,43) were enriched for geneprobes that were down-regulated in UC compared to both Control and ileal CD samples. Three clusters (#7, 26,41) were enriched for gene-probes that were up-regulated in UC compared to both Control and ileal CD samples.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…DNA concentration and quality were determined for each sample. Patients and controls' DNA was amplified for the three variants p.Arg702Trp, p.Gly908Arg, and p.L1007fsinsC of the NOD2 gene as previously reported (Nascimbeni et al, 2009). PCR products were sequenced using an ABI Prism 310 sequencer.…”
Section: Methodsmentioning
confidence: 99%